Disassociation In Sheriff Eric's Character In Thanksgiving 2023 - Imelza Novia Rakhmadani Pangestu; Rindrah Kartiningsih; Hariyono (PT. Gudang Pustaka Cendekia, 2025)
Disassociation is stated by Karantzas’ through the lens of Jeff Rendell's Thanksgiving film script by analyzing the dynamics of disassociation from the characters' Shariff Eric in this movie script. This study aims to show how the rejection of human nature, manifested through the denial of emotion, warmth, and flexibility, can lead to the experience of dissociation and its psychological and emotional consequences. Thanksgiving movie script is a massacre thriller movie script which is motivated by an endless sense of revenge, which is carried out by the character Sheriff Eric. He has lost a loved one and his future, as a result of thanksgiving night at that time. Then what about the concept of disassociation related in Jeff Rendell Thanksgiving movie script? Through qualitative methods, this study explains how the rejection of human nature. In conclusion, this story shows how a person can lose their humanity.